Evaluation Of Volunteer Care Recipient And Caregiver Experiences In Ventura County - Luna, Brandon; Forbes, Carmele; Morris, Bailey; Rosales, Stephanie; Berkowsky, Ronald (CBR@CSUCI: An annual volume of community-based research, 2025)
While much research has focused on paid and family caregiving, little has been devoted to exploring the impacts of volunteer caregiving (i.e., unpaid services provided by community volunteers). Volunteer caregiving can provide a viable alternative to paid and family caregiving when such services are too costly or unavailable, and volunteer caregiving has the potential to positively impact both care recipients and volunteers. Utilizing a community-based approach, students of a senior-level Health Science Capstone class at California State University Channel Islands examined services offered by a local volunteer caregiving organization and evaluated the experiences of caregivers and care recipients. Data came from mail-in surveys administered to care recipients (2008-2011, 2022) and volunteers (2022) through the nonprofit Caregivers (Ventura County, CA). Analysis of quantitative and qualitative data from care recipients (N= 394) showed that care recipients most frequently utilized transportation services, reported a positive relationship with their volunteers, were worried about financial and physical independence, and enjoyed services (particularly intergenerational programming). Analysis of quantitative and qualitative data from volunteers (N= 47) showed that many were older adults themselves, most often provided transportation, and were overwhelmingly satisfied with their participation with Caregivers. Findings show that volunteer caregiving organizations provide a vital resource for community-dwelling older adults and an avenue for civic engagement among community members.